High Intensity Pulsed Magnetic Field Application in Patients with Chronic Prostatitis Complicated by Erectile Dysfunction: а Randomized Prospective Study - Detelina B. Kulchitskaya; Anatoliy D. Fesyun; Vladimir A. Kiyatkin; Tatyana V. Konchugova; Maxim Yu. Yakovlev; Igor P. Bobrovnitsky (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2022)
INTRODUCTION. Chronic prostatitis is one of the most common urological nosologies, the third most common diagnosis in men under 50 years old. Existing scientific sources testify to the effectiveness of various physiotherapeutic interventions in patients with infectious-inflammatory diseases of the male reproductive system, complicated by erectile dysfunction. AIM. The aim of the study was the scientific substantiation of high-intensity pulsed magnetic field application in patients with chronic prostatitis complicated by erectile dysfunction. MATERIAL AND METHODS. The study included 60 patients randomized into two groups. The first group (30 people) received high-intensity pulsed magnetic field; the second group (30 people) received drug therapy. RESULTS AND DISCUSSION. It was shown that the high clinical results of high-intensity pulsed magnetic field application were based on the compensation of local blood circulation conditioned by the improvement of the prostate blood flow according to the ultrasound of the prostatic vessels as well as by the elimination of the penile blood supply deficiency due to the improvement of the arterial vessels tone and elimination of venous stasis according to laser doppler flowmetry. CONCLUSION. An innovative method has been developed to treat patients with chronic prostatitis complicated by erectile dysfunction using high-intensity pulsed magnetic field.